2009
DOI: 10.1016/j.brainres.2009.03.009
|View full text |Cite
|
Sign up to set email alerts
|

Retinal light input is required to sustain plasma melatonin rhythms in Nile tilapia Oreochromis niloticus niloticus

Abstract: The aim of this work was to confirm previous findings suggesting that the eyes are required for night-time melatonin production in Nile tilapia and further characterise this divergent circadian organisation. To do so, melatonin levels were firstly measured in eyecups and plasma to determine circadian patterns of melatonin production.Secondly, the effect of partial ophthalmectomy on the suppression of melatonin production was determined in vivo as well as ex vivo pineal light/dark sensitivity.Finally, to invest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 51 publications
1
7
0
Order By: Relevance
“…These results were similar to the in vivo results. This is in agreement with Martinez-Chavez and Migaud (2009), who reported that the pineal organ of the Nile tilapia Oreochromis niloticus niloticus was photosensitive and, when placed in vitro, increased night-time melatonin levels. We hypothesize that the observed increase in ZT16 and 40 means that photosensitivity was stimulated in the night-time as culture time passed.…”
Section: Discussionsupporting
confidence: 91%
“…These results were similar to the in vivo results. This is in agreement with Martinez-Chavez and Migaud (2009), who reported that the pineal organ of the Nile tilapia Oreochromis niloticus niloticus was photosensitive and, when placed in vitro, increased night-time melatonin levels. We hypothesize that the observed increase in ZT16 and 40 means that photosensitivity was stimulated in the night-time as culture time passed.…”
Section: Discussionsupporting
confidence: 91%
“…These two models, however, are only based on the pineal gland and do not consider the potential integrated role of the retina as is seen in other vertebrates. When this is taken into account and work on tropical species such as O. niloticus , O. mossambicus and C. gariepinus is included, then at least three models can be proposed from a pineal‐centred system in salmonids to a mammalian‐like centralized organisation in O. niloticus and C. gariepinus (Migaud et al , 2007; Martinez‐Chavez et al , 2009; Nikaido et al , 2009). In these later species, melatonin production was shown to rely predominantly on photic information perceived by the eyes.…”
Section: Photoperiod and Circadian Axismentioning
confidence: 99%
“…Because in mammals, the photic information is transduced by a photoneuroendocrine network composed of the retina, suprachiasmatic nuclei (SCN), and pineal gland (Falcón et al, ; Migaud et al, ), the input of environmental illumination through the eyes appears to be an essential route. In some tropical teleost species such as the Nile tilapia Oreochromis niloticus and African catfish Clarias gariepinus , photic information perceived by the eyes has a predominant impact on melatonin production (Migaud et al, ; Martinez‐Chavez and Migaud, ). Moreover, the pineal gland and eyes are necessary for sustaining the full amplitude of plasma melatonin rhythms in the European seabass and Atlantic cod Gadus morhua (Bayarri et al, ; Migaud et al, ).…”
Section: Discussionmentioning
confidence: 99%